Elevated Levels of Lead (Pb) Identified in Georgian Spices - Bret Ericson (Ubiquity Press, 2020)
Background: Human lead (Pb) exposure can result in a number of adverse health outcomes, particularly in children. Objective: An assessment of lead exposure sources was carried out in the Republic of Georgia following a nationally representative survey that found elevated blood lead levels (BLLs) in children. Methods: A range of environmental media were assessed in 25 homes and four bazaars spanning five regions. In total, 682 portable X-Ray Fluorescence measurements were taken, including those from cookware (n = 53); paint (n = 207); soil (n = 91); spices (n = 128); toys (n = 78); and other media (n = 125). In addition, 61 dust wipes and 15 water samples were collected and analyzed. Findings: Exceptionally high lead concentrations were identified in multiple spices. Median lead concentrations in six elevated spices ranged from 4–2,418 times acceptable levels. Median lead concentrations of all other media were within internationally accepted guidelines. The issue appeared to be regional in nature, with western Georgia being the most highly affected. Homes located in Adjara and Guria were 14 times more likely to have lead-adulterated spices than homes in other regions. Conclusions: Further study is required to determine the source of lead contamination in spices. Policy changes are recommended to mitigate potential health impacts. The results of this study contribute to a growing body of evidence that points to adulterated spices as a significant source of human lead exposure.